The general movement optimality score: a detailed assessment of general movements during preterm and term age. (14th September 2015) - Einspieler, Christa; Marschik, Peter B; Pansy, Jasmin; Scheuchenegger, Anna; Krieber, Magdalena; Yang, Hong; Kornacka, Maria K; Rowinska, Edyta; Soloveichick, Marina; Bos, Arend F
Abstract : Aim: To explore the appropriateness of applying a detailed assessment of general movements and characterize the relationship between global and detailed assessment. Method: The analysis was based on 783 video recordings of 233 infants (154 males, 79 females) who had been videoed from 27 to 45 weeks postmenstrual age. Apart from assessing the global general movement categories (normal, poor repertoire, cramped‐synchronized, or chaotic general movements), we scored the amplitude, speed, spatial range, proximal and distal rotations, onset and offset, tremulous and cramped components of the upper and lower extremities. Applying the optimality concept, the maximum general movement optimality score of 42 indicates the optimal performance. Results: General movement optimality scores (GMOS) differentiated between normal general movements (median 39 [25–75th centile 37–41]), poor repertoire general movements (median 25 [22–29]), and cramped‐synchronized general movements (median 12 [10–14]; p <0.01). The optimality score for chaotic general movements (mainly occurring at late preterm age) was similar to those for cramped‐synchronized general movements (median 14 [12–17]). Short‐lasting tremulous movements occurred from very preterm age (<32wks) to post‐term age across all general movement categories, including normal general movements. The detailed score at post‐term age was slightly lower compared to the scores at preterm and term age for both normal ( p =0.02) and poor repertoire general movements ( p <0.01). Interpretation: Further research might demonstrate that the GMOS provides a solid base for the prediction of improvement versus deterioration within an individual general movement trajectory. What this paper adds: General movement optimality score (GMOS) differentiates between normal, poor repertoire, and cramped‐sychronized general movements. Short‐lasting tremulous movements occurred from very preterm age to post‐term age. This was the case across all categories including normal general movements. GMOS post‐term was lower compared to the scores at preterm/term age. This held true for both normal and poor repertoire general movements. This article is commented on by Crowle on pages323–324 of this issue.